Belajar Literasi Dan Memupuk Rasa Percaya Diri Anak Di LSM KOPA, Medan Maimun - Ramadani Safitri; Agus Suriadi (Sekolah Tinggi Pastoral Kateketik Santo Fransiskus Assisi, 2023)
According to the KBBI, the meaning of literacy itself, as reported on the Ministry of Education and Culture's official website, is the ability to write and read. Etymologically, the term literacy itself comes from the Latin